In search of stability - Sivramkrishna, Sashi, author. (London)
1 online resource
Keywords: In Search of Stability seeks to understand the economics of money through a narrative on the history of the rupee. The period delineated for study is from the time of introduction of the rupee by Sher Shah Suri in 1542 up to 1971, the year which marked the beginning of the end of the Bretton Woods era and a fixed exchange rate regime. The underlying thread that runs through the narrative is the positive economics of money and history of the rupee. This is a book that explains what happened rather than raising normative questions on what ought to have happened or what could have been a more appropriate monetary system for India. The economics of money also draws us into understanding the evolution of monetary instruments through history and their impact on the economy. These instruments cannot be separated from the institutions that develop and are developed by them. A digression into a study of the origins, nature and development of some of the most important monetary institutions in India has therefore been included in this study. While standards of living have risen enormously, money has struggled to maintain its value across place and time, without definitive success. This has brought with it crises and severe hardship to entire societies; a lesson which the history of the Indian rupee unequivocally reveals.